CircRNA-100338 Is Associated With mTOR Signaling Pathway and Poor Prognosis in Hepatocellular Carcinoma - Huang, Xiu-Yan; Huang, Zi-Li; Zhang, Ping-Bao; Huang, Xin-Yu; Huang, Jin; Wang, Hong-Cheng; Xu, Bin; Zhou, Jian; Tang, Zhao-You (Frontiers in Oncology, 2019)
Background Hepatocellular carcinoma (HCC) is the leading cause of cancer-related deaths worldwide. Despite advances in the diagnosis and treatment of HCC, incidence and mortality continue to rise. For accurate diagnosis and treatment of HCC, there is an urgent need to precisely understand the molecular mechanisms underlying HCC tumorigenesis and progression. Accumulating evidence showed that circRNAs, which are normally produced by scrambling of exons at the splicing process, are recognized as a novel class of endogenous noncoding RNA, which have microRNA sponging properties. Objectives We aim to investigate the circRNA-100338 mediated downstream pathway, and evaluate its association with clinicopathological parameters. Methods The interaction between miR-141-3p and RHEB was predicted by miRanda, combined with the reverse correlation of expression levels. The components of mTOR signaling pathway, RHEB and EIF5, mediated by circRNA-100338 were evaluated by knockdown and overexpression of circRNA-100338, quantitative real-time PCR (qRT-PCR), and immunohistochemistry (IHC). Correlation significance of RHEB and EIF5 expression with clinicopathological parameters of HCC patients was calculated by Chi-squared test. Results Integrated analysis of circRNA-100338, miR-141-3p, and target genes revealed that RHEB, a key regulator in mTOR signaling pathway, was the target of miR-141-3p in hepatis B-related HCC. CircRNA-100338 regulates the activity of mTOR signaling pathway in vitro. IHC analysis revealed that mTOR signaling pathway was more active in HCC tissues with elevated circRNA-100338 expression. These results indicated that circRNA-100338 could regulate mTOR signaling pathway through circRNA-100338/miR-141-3p/RHEB axis. Finally, correlation analysis of RHEB and EIF5 expression with clinicopathological parameters of HCC patients revealed that the circRNA-100338, RHEB and EIF5 were indicators of poor prognosis in hepatis B-related HCC. Conclusion Elevated circRNA-100338 activates mTOR signaling pathway in HCC via circRNA-100338/miR-141-3p/RHEB axis and associates with poor prognosis of hepatis B-related HCC patients.